A study protocol for a pragmatic pre-post trial to determine the feasibility and effectiveness of a novel co-designed service to support health and wellbeing of older carers of older people - Aislinn Lalor; Susan Slatyer; Elissa Burton; Christina Bryant; Déborah Oliveira; Anjali Khushu; Natasha Brusco; Natasha Layton; Den-Ching Angel Lee; Belinda Cash; Jacqueline Allen; Lisa Licciardi; et al. (PLoS ONE, 2025)
Older carers (≥50 years) of older people (≥65 years) are an important sub-group of carers performing valuable roles in providing informal care but often do not have the time or give priority to supporting their own health and wellbeing. Current services supporting older carers’ health and wellbeing are fragmented and inadequate. Through previous research and co-design activity by our team, an innovative multidisciplinary Carer Health and Wellbeing Service (CHWS) has been developed. The purpose of this protocol paper is to describe the rationale for the CHWS and the methods proposed to evaluate its effectiveness and implementation outcomes. The CHWS commenced in March 2024 at Peninsula Health, Melbourne, Australia. Older carers of older people can be referred from multiple sources, including self-referral. A pre-post mixed methods study design is being utilised. Initial assessments include the Carer Support Assessment Needs Tool (CSNAT) and carer prioritisation of their needs, which guides further assessment and interventions. Assessments will occur at Service intake and 6 months later. The primary effectiveness outcome is the Preparedness for Caregiving Scale, and primary implementation outcomes are reach and adoption. Interviews of carers, referrers and staff, and a cost-utility analysis will be undertaken. The target sample size is 137 carers undertaking assessment and intervention over the 15 months data collection. Generalised linear regression will be used to compare pre- and post-continuous outcome measures. Qualitative data will be thematically analysed. Results will inform future scaling up of this innovative approach to optimising health and wellbeing of older carers of older people. Trial registration number: Australian New Zealand Clinical Trials Registry (ANZCTR) – ACTRN: 12625000245493.